1992
DOI: 10.1111/j.1096-0031.1992.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the Subfamilies of the Family Braconidae (Hymenoptera: Ichneumonoidea): A Reassessment

Abstract: Abstract— The recently published phylogeny of Braconidae by Quicke and van Achterberg is reassessed. Character‐state definitions and character polarities are evaluated, and more rigorous methods are suggested. Our results indicate that there are many more parsimonious solutions to their data set, the consensus of which differs substantially from their results. Based on our reassessment, little can be said about the relationships among braconid subfamilies. Consensus trees show the cyclostomes as a largely unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
9

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 40 publications
3
80
0
9
Order By: Relevance
“…More importantly, our finding represents the most basal phylogenetic placement of a mode of sex determination other than sl-CSD in the family Braconidae. The Doryctinae (to which H. prosopidis belongs) is considered basal to the Braconinae (van Achterberg, 1984;Quicke and van Achterberg, 1990;Wharton et al, 1992;Belshaw et al, 1998), where CSD was discovered in various species of Habrobracon (Whiting, 1961;Holloway et al, 1999;Weiser et al, 2004). The pattern of CSD that is beginning to emerge in the Braconidae could be explained by one of two hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, our finding represents the most basal phylogenetic placement of a mode of sex determination other than sl-CSD in the family Braconidae. The Doryctinae (to which H. prosopidis belongs) is considered basal to the Braconinae (van Achterberg, 1984;Quicke and van Achterberg, 1990;Wharton et al, 1992;Belshaw et al, 1998), where CSD was discovered in various species of Habrobracon (Whiting, 1961;Holloway et al, 1999;Weiser et al, 2004). The pattern of CSD that is beginning to emerge in the Braconidae could be explained by one of two hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we determine whether single-locus CSD operates in the braconid Heterospilus prosopidis Viereck, which is in the subfamily Doryctinae, itself considered to be basal to the Braconinae, and therefore near the base of the braconid clade (Wharton et al, 1992). A previous unpublished test of CSD in H. prosopidis was inconclusive due to difficulties in assessing developmental mortality and the lack of a true outcross, but failed to find an increase in the frequency of male production with generations of inbreeding (Cook, 1991;J Cook, personal communication).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent phylogenetic studies have shown aphidiines to be a lineage within the Braconidae (Quicke & van Achterberg, 1990, 1992Wharton et al, 1992), but it still remains unclear that to which of the many braconid subfamilies the aphidiines are most closely related.…”
Section: Introductionmentioning
confidence: 99%
“…These determinations were based on various keys, including Delvare and Aberlenc (1989) for insect families in general, White (2006) and White and Elson-Harris (2004) for fruit flies, Wharton and Gilstrap (1983) and Wharton et al (1992) for parasitoïds. The monographs of Bordat and Arvanitakis (2004) and Bordat and Daly (1995) were also used.…”
Section: Identification Methodsmentioning
confidence: 99%